Macrophages Mediate Increased CD8 T Cell Inflammation During Weight Loss in Formerly Obese Mice - Surendar, Jayagopi; Karunakaran, Indulekha; Frohberger, Stefan J.; Koschel, Marianne; Hoerauf, Achim; Hübner, Marc P. (Frontiers in Endocrinology, 2020)
Even after successful weight reduction, obese adults tend to quickly regain the lost weight. This raises the question of whether weight loss improves the underlying chronic adipose tissue inflammation characteristic of obesity. In order to improve our understanding of the mechanisms that reshape metabolic organs during weight loss, we investigated the macrophage and T cell function of the liver and adipose tissue on reversing high fat diet (HFD) mice to normal control diet (NCD). Obese mice that were switched to NCD showed an improvement in their metabolic profile that included enhanced glucose and insulin tolerance, decreased cholesterol, triglyceride, serum glutamic-oxaloacetic transaminase (SGOT) and serum glutamic pyruvic transaminase (SGPT) levels that were comparable to NCD controls. However, despite weight loss, increased frequencies, but not total numbers, of IL-17+ and IL-22+CD4+ T cells, IFN-γ+ and TNF+CD8+ T cells and IL-17+ and IL-22+CD8+ T cells were observed in the adipose tissue of mice switched from HFD to NCD compared to NCD and even HFD fed mice. Further, in the liver, IFN-γ+ and TNF+CD8+ T cell, IL-17+ and IL-22+CD8+ T cell, macrophage frequencies and their expression of antigen presenting molecules were increased. To determine if macrophages are the major determinants of the sustained inflammation observed during weight loss, we depleted macrophages, which significantly reduced IFN-γ+, TNF+, IL-17+, and IL-22+ CD8+ T cell frequencies in the liver and the adipose tissue. In conclusion, we show that although weight loss improves the metabolic profile, there is an active and ongoing CD8+ T cell inflammation in liver and adipose tissue mediated by macrophages.